Spontaneous bisphosphonate-related osteonecrosis of the left hemi-mandible: Similarities with phossy jaw - Giuseppina Campisi; Domenico Compilato; Itro Angelo; Lorenzo Lo Muzio; Giuseppe Colella (Wolters Kluwer Medknow Publications, 2012)
Intravenous bisphosphonates (BP) play a key role in the treatment of bone metastases. As a long-term side effects BP, a form of avascular osteonecrosis of the jaw has been reported. Although, invasive oral local procedures are often present in clinical history of patients suffering from bisphosphonates-related osteonecrosis of the jaws (BRONJ), about up to 50% of BRONJ are spontaneous. We report a case of a 68-year-old female with a spontaneous wide bone sequestration of the left mandibular body onset after infusion of zoledronic acid for 18 cycles for osseous metastasis due to metastatic anaplastic thyroidal carcinoma. Surprisingly the clinical aspects of the patient initially reminded us of the famous pathology described in 1899 called phossy jaw. This case is remarkable not only for the spontaneity of the osteonecrosis, but, above all, for the clinical similarity with cases of phossy jaw, described for the first time in the literature, thereby suggesting a potential common pathogenesis.